CHALLENGES OF TRANSLATING "WEAPONS OF MASS INSTRUCTION" INTO UZBEK - Sevarakhon Dekhkonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Translating the phrase "weapons of mass instruction" into Uzbek presents significant linguistic, cultural, and conceptual challenges. This article explores these challenges, emphasizing the complexities of maintaining the original meaning, tone, and impact in a different language and cultural context. By examining linguistic theories and practical translation strategies, we aim to provide insights into the difficulties of this specific translation task and offer solutions to preserve the phrase's intended nuances in Uzbek.